2010
DOI: 10.1186/1477-7827-8-40
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-initiated actions of estradiol (E2) in the regulation of LH secretion in ovariectomized (OVX) ewes

Abstract: BackgroundWe demonstrated that E2 conjugated to BSA (E2BSA) induces a rapid membrane-initiated inhibition of LH secretion followed hours later by a slight increase in LH secretion. Whether these actions of E2BSA are restricted to the pituitary gland and whether the membrane-initiated pathway of E2BSA contributes to the up-regulation of the number of GnRH receptors during the positive feedback effect of E2 were evaluated here. We have shown that the suppression of LH secretion induced by E2 and E2BSA is the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…We placed each male into a separate 5 gallon holding tank and measured milt volume again at 1 hr post-injection. E2:BSA, which cannot pass through the cell membrane, has been used in previous studies to assess the rapid effects of estradiol on cell surface receptors in preparations of fish testes (Loomis and Thomas, 2000) and neural tissue in several mammalian species (e.g., Abe and Terasawa, 2005;Arreguin-Arevalo et al, 2010;Temple et al, 2004). We conducted this experiment in June, when fish were in breeding condition.…”
Section: Bsa-conjugated Estradiolmentioning
confidence: 99%
“…We placed each male into a separate 5 gallon holding tank and measured milt volume again at 1 hr post-injection. E2:BSA, which cannot pass through the cell membrane, has been used in previous studies to assess the rapid effects of estradiol on cell surface receptors in preparations of fish testes (Loomis and Thomas, 2000) and neural tissue in several mammalian species (e.g., Abe and Terasawa, 2005;Arreguin-Arevalo et al, 2010;Temple et al, 2004). We conducted this experiment in June, when fish were in breeding condition.…”
Section: Bsa-conjugated Estradiolmentioning
confidence: 99%
“…Following the transient suppression of LH secretion, a preovulatory-like surge of LH was evident at approximately 12 h post-E2 infusion. In contrast, the E2-PEP and E2-BSA conjugates did not induce a preovulatory-like surge of LH; however, the mean LH measured during the surge window was significantly greater than that measured during the preinfusion period, suggesting that sensitivity of the pituitary gland may have increased at that time even through there was no increase in GnRH secretion [46].…”
Section: Discussionmentioning
confidence: 61%
“…The linkage of the large BSA molecule to the C-6 position of E2 has been shown to have differential effects in cells relative to free E2 [76,77]; however, in the present study, it was shown that E2-BSA increased GnRHR numbers in a manner similar to free E2. Other concerns have been raised that the bulkiness of BSA could alter the ability of binding of E2-BSA to the ER and alter the biological outcome [46,76]. That a greater concentration of E2-BSA was required to increase the numbers of GnRHR is not surprising because binding of E2-BSA to the soluble E2 receptor is only about 7% that of E2 (Arreguin-Arevalo and Nett, unpublished results).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations